Impact of the thickness on the optical and electronic and structural properties of sputtered Cu2S thin films - (:unkn) unknown (AIP Publishing, 2024)
A successful hexagonal Cu 2 S p-type semiconductor thin film using DC magnetron sputtering is reported. Films with thickness gradients were deposited by taking advantage of deposition geometry and target dimensions. X-ray diffraction (XRD) analysis confi...
Keywords: Películas delgadas; Propiedades ópticas